2014
DOI: 10.1111/tan.12368
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the 6‐digit level allele and haplotype frequencies of HLA‐A, ‐B, and ‐C in Koreans using ambiguity‐solving DNA typing

Abstract: Because Korean society is fast becoming multi-ethnic, the determination of ambiguous human leukocyte antigen (HLA) types using HLA allele frequencies is becoming less applicable. In this study, we focused on the development of new technical methods to directly resolve the ambiguities arising from HLA genotyping. One hundred and fifty unrelated healthy Korean adults were included in this study. All alleles from each HLA locus were first divided into 2-4 groups, with each group amplified in a single PCR tube (mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The base position of samples showing discrepant results between NGS and previous Sanger sequencing HLA genotypes obtained by Jun, et al [12] was confirmed using the BIOWI-THUS SBT Analyzer (Biowithus Inc., Seoul, Korea). Next, we performed PCR using primer sets (Avita Plus Kit, Biowithus Inc., Seoul, Korea) harboring the necessary additional exon and Sanger sequencing according to previous methods to confirm the sequence difference in the base position of the additional exon [12].…”
Section: Additional Exon Analysis Of Discrepant Ngs and 6-digit Resolmentioning
confidence: 53%
See 1 more Smart Citation
“…The base position of samples showing discrepant results between NGS and previous Sanger sequencing HLA genotypes obtained by Jun, et al [12] was confirmed using the BIOWI-THUS SBT Analyzer (Biowithus Inc., Seoul, Korea). Next, we performed PCR using primer sets (Avita Plus Kit, Biowithus Inc., Seoul, Korea) harboring the necessary additional exon and Sanger sequencing according to previous methods to confirm the sequence difference in the base position of the additional exon [12].…”
Section: Additional Exon Analysis Of Discrepant Ngs and 6-digit Resolmentioning
confidence: 53%
“…Samples were obtained by collecting 10-20 mL of venous blood from each subject, and the concentration of the extracted DNA was adjusted to 40-100 ng/µL. These samples were previously analyzed for 6-digit HLA types using Sanger sequencing with Big Dye Terminator 3.1 (ABI Inc., Foster City, CA, USA) and an ABI 3730 DNA analyzer (ABI Inc.) [12]. Samples were stored in a -70°C deep freezer until our analysis.…”
Section: Samples Collectionmentioning
confidence: 99%
“…HLA‐B*55 is relatively common in Orientals compared with other ethnic groups with an average frequency of 3.67% (0.0%‐22.6%) . High‐resolution genotyping of HLA‐B*55 has shown mostly B*55:02 (2.00%) in Koreans . Here, we report a novel HLA‐B*55 allele, officially named as B*55:81 , which was identified by cloning and sequencing in a Korean individual.…”
mentioning
confidence: 88%
“…HLA-C*03 is the most frequent allele with average frequency of 27.32% in the Korean population: C*03:02 (7.66%), C*03:03 (9.33%), and C*03:04 (10.33%). 1 Serological equivalence of C*03:03 is assigned as Cw9 which is different from Cw10 encoded by the C*03:02 and C*03:04 alleles. 2 Therefore, 4-digit level of HLA typing is necessary to assign split antigens for HLA-C*03 alleles.…”
mentioning
confidence: 99%